PP.09.23: ADRENAL PHEOCHROMOCYTOMA INCIDENTALLY DISCOVERED IN A PATIENT WITH PARKINSON'S DISEASE. (June 2015) - Petramala, L.; Concistré, A.; Marinelli, C.; Zinnamosca, L.; Iannucci, G.; De Vincentis, G.; De Toma, G.; Letizia, C.
Abstract : Objective: Pheochromocytoma (PHEO) and paragangliomas (PGLs) are neuroendocrine tumors arising from chromaffin cells, primarily found in the adrenal gland with an incidence of 1 to 6 per million and a prevalence in hypertension populations varies between 0.1 % and 0.6%. Approximately 4–15 % of PHEO are found as incidentalomas and later coherently diagnosed as PHEO. Design and method: The coexistence of PHEO and Parkinson's disease is very rare, with only three cases reported in English literature. Here, we report a case of 67-year-old male with Parkinson's disease under treatment of dopaminergic drugs, presented for evaluation of poorly controlled hypertension and right adrenal mass incidentally discovered. Results: The working included an endocrinological examination, which revealed higher 24h-urine metanephrines levels suggesting the possibility of a PHEO. Subsequently, scintiscan with I-123 – MIBG was performed confirming raised activity within the right adrenal gland concordant with the mass. An elective laparoscopic right adrenalectomy was performed and pathological examination confirmed the diagnosis of PHEO. Conclusions: We empathized the relevance of an accurate diagnosis especially in rare disease, and I-123- MIBG scintigraphy is diagnostic value for confirming PHEO in patient with Parkinson's disease while receiving dopaminergic therapy.